Preparticipation screening for cardiovascular abnormalities in competitive athletes: role of 12-lead electrocardiogram - Ania, J. M.; Carro, A.; Martin, M.; Reguero, J. J.; del Valle, M. E.; Hernandez, E.; Espolita, A. (Archivos de medicina del deporte, 2008)
The principal objective of screening is to reduce the cardiovascular risks associated with organized sports and enhance the safety of athletic participation. The effi cacy of the various athlete screening strategies is not easily resolved in the context of evidence-based investigative medicine Objective: Our objective is to evaluate the ability of electrocardiogram (EKG) as a part of preparticipation screening strategy in a sample of players from a local federation. Material and methods: 1052 players were evaluated from September 2006 to June 2008. In addition to medical history and physical examination, a 12 lead EKG was obtained. We followed positive criteria from European Society of Cardiology (ESC) on its consensus document (2005). Those with positive EKG criteria were referred for echocardiogram (Sonos 5500) or other diagnostic tests. Results: N=1052 (soccer: 825; basketball: 64, handball: 26, canoeing: 46, hockey: 29, volleyball: 24, gymnastics: 11, wrestling: 8, weightlifting: 6, karate: 4, athletics: 3, swimming: 2, ball: 4). 94.9% males; mean age, 20.3± 4.05 years; body mass index, 23±5.77. 73 players (6.9%) fulfi lled EKG criteria described by ESC. EKG fi ndings: repolarization abnormalities: 40 (ST depression, inverted T wave); voltage criteria: 5; right bundle branch block: 9; right axis: 7; left axis: 2; preexcitation syndrome: 4; ectopic ventricular complexes: 5; long QT: 1. Echocardiographic findings: interventricular septal thickness: 10.3 ± 1.3 mm (6.9-23); posterior wall thickness: 9.85±1.04 (8-14). 8 players showed a septal thickness =12 mm, defi ned as left ventricular hypertrophy, all of them with repolarization abnormalities. 5 of them were included in the "gray area"; 2 were considered "athlete`s heart"; the last one was diagnosed of hypertrophic cardiomiopathy, confi rmed by genetic testing. He was advised for discontinuation competitive sports. An exercise EKG was performed in 5 players (preexcitation syndrome and long QT), with normal findings. Conclusion: EKG is an easy, useful and available tool in preparticipation screening, raising suspicion of clinically relevant, preexisting abnormalities. Further diagnostic testing would confi rm or exclude diagnosis of hypertrophic cardiomyopathy as well as other potentially lethal conditions.